Model-driven software development integrating quality assurance - Bunse, Christian.; Rech, Jörg, 1968- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
Model-driven software development (MDSD) drastically alters the software development process, characterized by a high degree of innovation and productivity. However, quality assurance application in the domain of software models and model-driven software development is still in an emergent phase. This book provides in-depth coverage of important concepts, issues, trends, methodologies, and technologies in quality assurance for model-driven software development. This Premier Reference Source provides educators, researchers, and practitioners with a comprehensive overview of current trends in research and practice of quality assurance in MDSD.